Custodial Torture and Protection against Custodial Torture – An Overview: Understanding the psychological impacts and legal protection against custodial torture (Journal of Advances and Scholarly Researches in Allied Education, 2015)
“Torture is anguish queering in your chest, cold as ice and heavy as a stone, paralyzing as sleep and dark as the abyss. Torture is despair and fear and rage and hate. It is a desire to kill and destroy including yourself”.- Adriana P. Bartow1